2008
DOI: 10.1080/10641950802000950
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of White Coat Hypertension in Pregnant Women with Teletransmitted Home Blood Pressure

Abstract: In this population, WCH is very common and benign. HBP monitoring is feasible and well accepted. However, teletransmission is necessary for safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 19 publications
0
36
0
3
Order By: Relevance
“…Limited available data suggests that white coat HTN may affect from 30 to 70% of pregnant women [55, 56]. Compared to women with sustained HTN, defined as elevated office and out-of-office BP, women with white coat HTN had better pregnancy outcomes [5759].…”
Section: The Role Of Out-of-office Blood Pressure Measurement In Pregmentioning
confidence: 99%
“…Limited available data suggests that white coat HTN may affect from 30 to 70% of pregnant women [55, 56]. Compared to women with sustained HTN, defined as elevated office and out-of-office BP, women with white coat HTN had better pregnancy outcomes [5759].…”
Section: The Role Of Out-of-office Blood Pressure Measurement In Pregmentioning
confidence: 99%
“…[8][9][10][11] Self home blood pressure monitoring is more acceptable to pregnant women than more frequent clinic visits, hospital admission, or ambulatory monitoring. [12][13][14][15] Taylor et al found self-monitoringof blood pressure more acceptable than 24 hour ambulatory monitoring; in a study of 78 healthy pregnant women who evaluated both home and ambulatory monitors at 35-37 weeks gestation, as home monitoring caused less discomfort and did not interfere with activities or sleep. 16 In present study, none of the women reported any unwillingness to participate, nor any discomfort, or any difficulty in understanding the procedure or monitoring blood pressure.…”
Section: Will the Women Monitor Blood Pressure At Home?mentioning
confidence: 99%
“…Ainsi dans une étude réalisée chez 57 femmes enceintes hypertendues utilisant cette technique, 92 % la trouvaient facile avec des résultats bien supérieurs à ceux retrouvés dans l'HTA de l'adulte puisque 98 % des résultats étaient analysables. Cependant, l'automesure à l'inverse d'une surveillance en hospitalisation ou même sur 24 heures avec la MAPA nécessite de ne revoir la femme enceinte que plusieurs jours plus tard en la laissant mesurer elle même sa pression artérielle à domicile avec le risque de survenue d'une HTA sévère ou compliquée pendant cette surveillance à domicile [12]. Ainsi, il apparaît qu'il est peut être dangereux de laisser un appareil d'automesure à une femme enceinte hypertendue sans une équipe prête à la prendre en charge en cas d'aggravation et une bonne formation préalable.…”
Section: Avoir Des Conditions De Mesure Et D'interprétation Correctesunclassified